2019
DOI: 10.3390/sym11091109
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Differences among Ten Fingers in Force Control Capabilities by a Modified Meyer Model

Abstract: Quantifiable differences among fingers in force control capability have both important practical and theoretical values in characterizing force control of accurate finger-tapping tasks. Following the classical Fitts' law paradigm, we quantified the differences among ten fingers in term of speed-accuracy trade-off (SAT) in performing repetitive discrete force control tasks. Visual cues displaying targeted force magnitudes and tolerances were provided. Users were required to apply the targeted force within the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(108 reference statements)
1
2
0
Order By: Relevance
“…The experimental tests were conducted one by one to verify the two hypotheses, respectively, in two types of two-finger fine-force tasks. Our previous study confirmed that the performances of single-finger pressing were nearly equal for index and middle fingers in a discrete force control task (Peng et al, 2019). Consequently, in the current study, the index and middle fingers were employed as tapping fingers to minimize the difference between individual fingers.…”
Section: Task Designsupporting
confidence: 82%
See 2 more Smart Citations
“…The experimental tests were conducted one by one to verify the two hypotheses, respectively, in two types of two-finger fine-force tasks. Our previous study confirmed that the performances of single-finger pressing were nearly equal for index and middle fingers in a discrete force control task (Peng et al, 2019). Consequently, in the current study, the index and middle fingers were employed as tapping fingers to minimize the difference between individual fingers.…”
Section: Task Designsupporting
confidence: 82%
“…As shown in Figure 1, a customized platform for multifinger force acquisition was modified based on the single-finger force measurement system used in previous research (Peng et al, 2019). For each finger, the amplitude of finger force was measured by a force sensor (FSG15N1A, Honeywell International, Inc., Morris Plains, NJ) embedded in a customized rectangular box.…”
Section: Apparatusmentioning
confidence: 99%
See 1 more Smart Citation